Answer to ECG Quiz no.18 - Okreglicki, A (SA Heart Journal, 2017)
The patient context is important when commenting on or interpreting the ECG. Pulmonary embolism needs to be considered in any patient presenting with chest pain or haemodynamic instability, especially if the ECG does not show typical acute myocardial ischaemia or infarction. A multitude of ECG abnormalities, singly usually non-specific, strengthens the case for pulmonary embolism. A normal ECG does not exclude pulmonary embolism.